Synthesis of Visual and Verbal Elements in Vasily Kamensky’s Avant-Garde Poem “Palace of S. I. Shchukin” - O. V. Bogdanova (Научный диалог)
This paper offers an interpretation of the extraordinary poem “The Palace of S. I. Shchukin” by early 20th-century avant-garde poet Vasily Kamensky, taken from his 1914 collection of “reinforced concrete poems,” “Tango with Cows.” Utilizing the verbal-visual nature of this poem-painting, we examine a unique specimen of Futurist text. The analysis addresses the complex narrative devices that may challenge conventional perception within the poem's pictorial framework. Through an exploration of semantic categories inherent in the text, we provide a step-by-step analysis of the ekphrastic layer within the “reinforced concrete poem” “The Palace of S. I. Shchukin.” It is demonstrated that this poem-painting possesses a rigorous and systematic construction, a topographical sequence of narrative development, and a coherent compositional structure, all mediated by both the semantics of the depicted (the palace and its contents) and the “transversal” techniques characteristic of Kamensky's Futurist poetics. We propose interpretations for extracting various images reminiscent of modernist French painters (such as Matisse, Monet, Picasso, Cézanne, among others) from the text. Furthermore, it is emphasized that Kamensky's poem-painting embodies not only Futurist elements but also a distinctly everyday nature, suggesting that the avant-garde “zaum” culture within which the poet operated did not hinder the creation of a deeply poetic and readily accessible text.